Experimental investigation of immiscible supercritical carbon dioxide foam rheology for improved oil recovery - Ahmed, S. (China University of Geosciences, 2017)
This paper presents the rheological behaviour of supercritical CO2 (sCO2) foam at reservoir conditions of 1 500 psi and 80 °C. Different commercial surfactants were screened and utilized in order to generate a fairly stable CO2 foam. Mixed surfactant system was also introduced to generate strong foam. Foam rheology was studied for some specific foam qualities using a high pressure high temperature (HPHT) foam loop rheometer. A typical shear thinning behaviour of the foam was observed and a significant increase in the foam viscosity was noticed with the increase of foam quality until 85. A desired high apparent viscosity with coarse texture was found at 85 foam quality. Foam visualization above 85 showed an unstable foam due to extremely thin lamella which collapsed and totally disappeared in the loop rheometer. Below 52, a non-homogenous and unstable foam was found having low viscosity with some liquid accumulation at the bottom of the circulation loop. This research has demonstrated rheology of sCO2 foams at different qualities at HPHT to obtain optimal foam quality region for immiscible CO2 foam co-injection process. © 2017, China University of Geosciences and Springer-Verlag GmbH Germany.